Tribological behaviour of combined coatings deposited on aluminium - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2005)
In this paper the tribological performance of oxide (Cr2O3, ZrO2CaO and Al2O3) and combined coatings applied on a commercially pure aluminum sheet were presented. Combined coatings were produced by applying Polytetrafluoroethylene (PTFE) film on the oxide coatings. Among the oxide coatings Cr2O3 exhibited the highest and Al2O3 exhibited the lowest wear resistance, in accordance with their hardness. Combined coatings exhibited superior wear resistance than oxide coatings even at heavy wear testing conditions.
Keywords: ceramic; coating; polymer; wear; WEAR